Diferença de preços entre as espécies de ações negociadas na Bovespa: influência dos fatores governança corporativa, liquidez e política de dividendos - Gendelsky, Vanessa Rabelo Dutra (2007)
The present study has the objective of identifying the influence of the following factors: corporate governance, liquidity and dividend policy in the difference of prices between preferential and ordinary stocks of the Brazilian companies negotiated at Bovespa. To evaluate the corelation among the independent variables of each factor the monthly corelation among them was calculated. It was observed that the variables volume ant title are highly corelated. In order to avoid the multicolinearity problem the decision was to estimate regression models separated. The variable volume is also highly corelated to the variable business, which led to the decision of evaluating a third model with the variable business. However, for all the models the variable spread was maintained, since this hasn t presented high corelation with the other variables. The size of the company was also tested to analyse if there is a corelation with the difference of prices.Even not having a corelation it was found to be prudent to insert this measure in the models to be estimated. The analyses method is a monthly linear multiple regression. After the estimation of the coefficient of the regressions analysed between 1995 and 2006, 144 estimates of each b coefficient were obtained. Following the procedure suggested by Fama and MacBeth(1973) the average of regression coefficient for each factor was calculated. The t estatistical test was used to select the variables which reached significance in the test. The results show that model 3 is responsible for the three factors together. The liquidity is not the explanatory factor in the difference of prices neither for model 1 nor for 2. That is, the variables spread and volume or spread and title together are not capable to explain the influence of the prices. Therefore, the model that showed a higher efficiency is model 3